The effects of unintentional drowsiness on the velocity of eyelid movements during spontaneous blinks. (4th February 2021) - Johns, Murray; Hocking, Christopher
Abstract: Objective . Unintentional drowsiness, when we should be alert, as for example when driving a vehicle, can be very dangerous. In this investigation we examined the effects of unintentional drowsiness on the relative velocities of eyelid closing and reopening movements during spontaneous blinks. Approach . Twenty-four young adults volunteered to take part in this experiment, and 18 were finally accepted. They performed a 15 min visual reaction-time test at the same time of day and under the same environmental conditions with and without overnight sleep deprivation, one week apart. Their eyelid movements during blinks were monitored by a system of infrared reflectance blepharometry during each test. Main results . Very close relationships between the amplitude and maximum velocity of eyelid closing and reopening movements were confirmed. Frequency histograms of amplitude–velocity ratios (AVRs) for eyelid closing and reopening movements showed significant differences between alert and drowsy conditions. With drowsiness, eyelid movements became slower and AVRs increased for many but not all blinks. We also described a time-on-task effect on the relative velocities of eyelid movements which was more apparent in the drowsy condition. Eyelid movements became progressively slower during the first half of the test. This was presumably due to a short-lived alerting effect of starting the test. Significance . The relative velocity of eyelid closing and reopening movements during spontaneous blinks decreases with unintentional drowsiness but is sensitive to the brief alerting stimulus of starting a reaction-time test.